The National Stadium, Beijing. (Architects' Journal, 2004)
Discusses how a range of tools including computer-aided design visualization and rapid prototypes allowed the exploration of the complex form and geometry of the main stadium for the XXIX Olympiad to be held in Beijing, China in 2008. Design by a team of Herzog & de Meuron, ArupSport and China Architecture Research Group; Creation of a form that is pure structure with an almost archaic quality; Structural elements; Construction of the outer surface from three principal surfaces; Primary column; Facade elements.